When Touch Is Refused or Accepted in Art: A Comparison of Van Gogh’s The Sunflowers and Maurizio Cattelan’s The Comedian - Ying Wu (ESPES, 2025)
Moments of crisis are always worth analysing. When confronted by visitors’ hands, The Sunflowers and The Comedian represent contrasting attitudes. This divergence is determined by differences in their modes of existence, durations, irreproducibilities, and ways of being experienced. The existence of The Sunflowers depends upon the permanence of its physical substance; however, The Comedian is an ephemeral event, inhering in fluid relationships and forms of interactions. From the former to the latter, artworks have embodied a detachment from their Objecthood and are transforming from products into processes. The spectator’s experience also changes from the pure gaze to corporeal, emotional and behavioural engagement. Traditional museum provides a distanced space, reinforcing the untouchability of artworks by maintaining a separation between the spectator and the work, while The Comedian created an interactive space, where the sense of touch is not only corporeal, but also affective.